The effect of Hawkins’ method on achieving social studies for fifth grade primary school students - Hillel Lafta, Hassan; Hassan Mathqoor, Bushra (Al-Adab Journal, 2020)
The current research aims to identify (the effect of Hawkins’ method on the achievement of social studies for the fifth elementary pupils), and in order to verify the research goal, the researcher set the following hypothesis: There is no statistically significant difference at the level of significance (0,05), between the average pupil degrees The experimental group who studied the subject of social studies using the Hawkins method and the mean scores of the control group who study the same subject in the traditional way in the post achievement test. The researcher adopted the experimental approach and experimental design with the control group with the post test, and the research community determined the fifth primary school pupils in the government day and primary schools belonging to the six education directorates in Baghdad governorate, and the experiment was applied to the research sample that was represented by the fifth primary school pupils in the third chest school The Governmental Primary Day School for Boys, affiliated to the General Directorate of Rusafa Education for the second year, for the academic year (2019-2020), as it consisted of (65) students, with (32) students in the experimental group, which was studied according to the Hawkins method, and (33) students in the control group And that was studied according to the traditional method. The researcher has built the research tool of the post achievement test, where the test consisted of multiple of (30) items, the validity of the test was verified and the stability and calculation of psychometric properties were applied, and the test was applied after the completion of the experiment that took the first semester of the academic year (2019-2020), where It started on Thursday, corresponding to (10/10/2019), and ended with conducting the post-test on Thursday corresponding (19/1/2020). After calculating the test results by adopting the T-test for two independent samples, the result was: There is a statistically significant difference at the level (0,05) between the average score of students of the experimental group who are studying according to the Hawkins method, and the average score of students of the control group who study according to the traditional method of achievement in favor of the experimental group. Based on the result that the researcher reached a number of conclusions, including: 1- Teaching Hawkins method in the subject of social studies for fifth graders, has the effect of raising the level of academic achievement, compared to the traditional method. 2- Hawkins’ method has proven effective in making pupils a focus of the educational process, and this is what all modern teaching methods advocate. 3- Hawkins’ method focuses on the principle of collaborative work between students and their peers and the teacher, which leads to the exchange of information and the raising of the level of knowledge, then the role of the teacher will be a guide and a guide to their progress towards educational goals. 4- Teaching according to Hawkins’ method provides more opportunities for students to express themselves effectively. In light of the research results, the researcher recommended recommendations, including: 1- Adopting Hawkins’ method of teaching social studies at the primary stage, for its role in raising the level of achievement for students. 2- Preparing and preparing classrooms to help the teacher teach according to the Hawkins method, as the researcher faced some difficulties in preparing the classroom